Visual Expression of Children with Special Needs in SLB Muhammadyaah Surya Gemilang in the Image of the Picture - Arindy Sabilla Dewi; Eko Sugiarto (Universitas Negeri Medan, 2023)
Analysis of Visual Expression in Images of Children with Special Needs is one form of observation and research on the characteristics of pictures of children with special needs. Children with special needs are very synonymous with visual language rather than spoken language. How children express their creativity and work in a picture, where the picture of every child who has certain deficiencies and disability certainly has the meaning, uniqueness and characteristics of each in expressing art. Some images show various image periodizations. Some show unique image typography. This study was conducted to find out whether a person's deficiencies or disability can affect the creativity and style of drawing children with special needs. Research uses a qualitative approach with a case study design, which will be carried out at SLB Muhammadiyah Surya Gemilang. Research uses controlled observation techniques, interviews with teachers and document studies. In this SLB there are several different disabled classes. Among them such as mental retardation, disabilities, deaf, and autism. The data to be analyzed in the form of images from children with special needs that have been selected for further research in it. The results of this study, children with special needs based on the shortcomings and disability suffered have their own characteristics based on their use, so that the expression of pictures of children with special needs under certain conditions has differences in both ideas and visualization of images